2018
DOI: 10.1002/app.46460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different catalysts on the structure and properties of polyurethane/water glass grouting materials

Abstract: Polyurethane/water glass (PU/WG) grouting materials were prepared in presence of different proportions of catalyst. The effects of catalyst on the mechanical properties, thermal properties, and chemical cross‐sectional morphologies of the grouting materials were also investigated. Catalyst addition can significantly increase the chemical reaction rate, reduce the gel time and curing time, and improve the thermal stability of PU/WG grouting materials. It was found that the grouting material containing 0.1 wt % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 58 publications
0
41
0
1
Order By: Relevance
“…2(f) appears to be more compact than that depicted in Fig. 2(e) [23][24][25][26]. These difference in the microstructures of the cementitious materials clearly resulted in different strengths.…”
Section: Advances In Engineering Research Volume 176mentioning
confidence: 99%
“…2(f) appears to be more compact than that depicted in Fig. 2(e) [23][24][25][26]. These difference in the microstructures of the cementitious materials clearly resulted in different strengths.…”
Section: Advances In Engineering Research Volume 176mentioning
confidence: 99%
“…The compressive strength, fracture toughness, fracture energy, flexural strength and bending die of PU/WG grouting material were increased by 11.65–40.65%, 9.68%, 21.33%, 6.60% and 15.85%, respectively, by introducing 2.5 wt.% silane coupling agent 3-chloropropyltrimethoxysilane (CTS) (Figure 25). Zhang et al [114] discussed the effects of dimethylbenzylamine (BDMA) and dibutyltin dilaurate (DBTDL) catalysts on the PU/WG grouting material. DBTDL accelerated the gel and curing reaction of the materials and BDMA increased the fluidity and compressive strength of the PU/WG.…”
Section: Polymer-containing Soft Matters For Coal Mine Disaster/hamentioning
confidence: 99%
“…In recent years, various modified polyurethane materials had been developed for different application ways. It was found that the catalyst had a great influence on the polyurethane grouting material by Q. Zhang et al A small amount of catalyst can improve the reaction speed and early strength of the polyurethane grouting material [21]. Adding nano-silica to polyurethane grouting material can improve the toughness of www.videleaf.com materials and enhance the mechanical properties of high temperature and low temperature [22].…”
Section: Introductionmentioning
confidence: 99%